Rosemary Radford Ruether, Integrating Ecofeminism, Globalization and World Religions - Grau, Marion (Journal for the study of religion, nature and culture, 2006)
Rosemary Radford Ruether, Integrating Ecofeminism, Globalization and World Religions (Lanham: Rowman & Littlefield, 2005), pp. xii + 194. Paperback $20, £14.99, ISBN 0-7425-3530-4.